Purification of food industry sewage by means of bioplateau constructions - Булавенко, Р. В.; Степова, О. В.; Рома, В. В. (Scientific Progress & Innovations, 2012)
On the base of already existing phytotechniques, in particular the usage of higher aquatic plants in bioplateau constructions and other advanced methods, there was developed an effective, ecological system of post processing dairy products sewage purification for the reusable resource. A two-stage bioplateau construction with higher aquatic plants (Reeds, Reeds Lake, Lesser Bulrush, Common Bulrush, Sweet Flag) was offered. There was a bioplateau with higher water plants for purification of dairy industry sewage as a reusable resouce for the company needs worked out.